Control of High-Power Wind Energy Conversion System Fed by Multi-level Converters. (July 2017) - Errami, Youssef; Obbadi, Abdellatif; Sahnoun, Smail; Barara, Mohamed; Ouassaid, Mohammed; Maaroufi, Mohamed
Abstract: The progress of Variable Speed Wind Turbine Systems (VS-WTS) is currently focused in reaching higher power ratings (8MW). Also, medium voltage operation is at this power level, particularly at electrical network, a required feature. Consequently, high power medium-voltage multilevel converters for VS-WTS have been attracting more and more attentions. Nevertheless, most modern high-power VS-WTS consist of a large number of Wind Turbine Generators (WTGs) connected and operating simultaneously to reach the multi-megawatt level. This study presents a control strategy for a grid-connected onshore wind farm based Permanent Magnet Synchronous Generator (PMSG), where cascaded multilevel converters are employed on the generators and grid side. The generator-side converters provide speed control of the turbine-generator units to implement Maximum Power Point Tracking. The grid side Neutral Point diode Clamped (NPC) converter system regulates reactive and real power flow to the electrical network. So, it regulates the dc bus voltage and the ac side power-factor. The modulation technique for the proposed topology is developed from Space Vector Modulation. The overall control approaches of a rectifiers and an NPC are also described. Nonlinear Sliding Mode technique (NL-SM) with speed control and Vector Oriented Control are developed. To validate the proposed approaches, simulations are carried out on a high-power wind energy conversion system with multi-level converters and MATLAB/Simulink software. The simulation results demonstrate a good performance in diverse scenarios.